The Semantic and Syntactic Range of Old English Nominalisations with Aspectual Verbs - Ojanguren López, Ana Elvira (Journal of English Studies, 2023)
This article analyses the complementation of Old English verbs of aspect by means of nominalisations. Three types of derived nominals are distinguised: deverbal nominals that entail a verbal predication but do not take complements of their own; direct nominalisations (with Actor or Undergoer genitive); and oblique nominalisations. The main conclusion of the article is that, to the sources of the English gerund identified by Lass (1992), others should be added, including suffixes (such as -ung, -ness and -t) and affixless derivation from strong and weak verbs. It is also a conclusion of this study that Old English already provides evidence of the acquisition of verbal properties by deverbal nominalisations, such as nominalisations with direct objects and voice distinctions.